Synthesis, characterization, and evaluation of a selective molecularly imprinted polymer for quantification of the textile dye acid violet 19 in real water samples - Luna Quinto, Miguel (2020)
A molecularly imprinted polymer (MIP) was developed for the determination of acid violet 19 (AV19) dye. The MIP was synthesized by polymerization using 1-vinyl imidazole (functional monomer) and 2,2′-azobis(2-methylpropionitrile) as the radical initiator. The functional monomer was previously selected by computational simulations. The MIP adsorption data could be fitted using the Langmuir model obtained a Qm value of 6.93 mg g−1 and 2.84 mg g-1 for the corresponding non-imprinted polymer (NIP) and the process followed pseudo-second-order kinetics (k2 0.2416 mg g−1 min−1 MIP). The BET specific surface areas were 229.6 m2 g−1 and 28.6 m² g−1, to MIP and NIP, respectively. Analyses showed that the material provided excellent selectivity towards acid violet 19 (AV19) when compared to other analytes including Acid Violet 17 (AV17), Tartrazine (TZ), Acid Red 14 (AR14), Patent blue-VF (PBV), Sunset yellow FCF (SY) and Acid Red 1 (AR1). The calculated Kd value for the MIP was 0.116 L g−1 and the imprinting factor was 2.89. This alternative and effective material for the enrichment, extraction, and determination of acid violet 19 presents in complex real samples was applied using two different rivers water and industrial effluent, with excellent recoveries values ranging between 85% up to 99%.